2015
DOI: 10.5152/tjar.2015.50023
|View full text |Cite
|
Sign up to set email alerts
|

Late Local Anaesthetic Toxicity After Infraclavicular Block Procedure

Abstract: Local anaesthetic (LA) toxicity is the most fatal complication of peripheral nerve block techniques. Accidental intravascular application or use of doses above the safety range are the most common cause of toxicity. Bupivacaine is a long-acting LA frequently used for long procedures or those associated with significant post-procedural pain. Fatal central nervous system and cardiovascular system toxicity are described. In this paper, we reported a young patient who showed LA toxicity symptoms 7 h after an infra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
4
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 11 publications
0
4
0
1
Order By: Relevance
“…The patient experienced seizures 1 h after injection of local anesthetics but no cardiovascular system symptoms. İnceöz et al [ 6 ] reported LAST that occurred 7 h after infraclavicular BPB single injection. However, they used bupivacaine and prilocaine, which have longer half-lives than the local anesthetics used in our cases and the total amount of drugs used was also large (0.5% bupivacaine 11.25 ml, 56.25 mg + 2% prilocaine 11.25 ml, 225 mg).…”
Section: Discussionmentioning
confidence: 99%
“…The patient experienced seizures 1 h after injection of local anesthetics but no cardiovascular system symptoms. İnceöz et al [ 6 ] reported LAST that occurred 7 h after infraclavicular BPB single injection. However, they used bupivacaine and prilocaine, which have longer half-lives than the local anesthetics used in our cases and the total amount of drugs used was also large (0.5% bupivacaine 11.25 ml, 56.25 mg + 2% prilocaine 11.25 ml, 225 mg).…”
Section: Discussionmentioning
confidence: 99%
“…While toxicity symptoms occur in the first 50 seconds in 50% of cases, it was revealed that 75% of cases had clinical findings of toxicity symptoms within the first five minutes [ 1 ]. The incidence of early-onset local anesthetic toxicity varies from 0.04% to 0.18%, while late-onset toxicity findings are encountered more rarely in the literature [ 5 - 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…In situations where the cardiovascular system is affected, it is necessary to begin treatment with IV lipid solutions immediately to increase the success of resuscitation [ 9 ]. Most practitioners may consider administering lipid infusion in order to prevent cardiovascular system involvement in a seizure patient.…”
Section: Discussionmentioning
confidence: 99%
“…LAs complications have been reported in a wide range from simple allergic conditions to cardiovascular and neurological complications that can be fatal (3,7). There are also cases that have been successfully treated following the recommendations of the clinical guidelines (8)(9)(10). Protocols for ensuring airway safety, assessment of circulation, and intravenous lipid emulsion (ILE) treatment are included in LAST treatment (3,7).…”
Section: Introductionmentioning
confidence: 99%